Flexible inorganic perovskite solar cell based on sulfonic ionic liquid additive
By introducing sulfonic acid-based ionic liquid additives into inorganic perovskite films, reducing the preparation temperature and homogenizing the Cs elements, the problem of incompatibility of all-inorganic perovskite solar cells with flexible substrates at high temperatures is solved, and high quality is achieved Low temperature preparation of films and excellent device performance.
Patent Information
- Application Number
- CN202411149088.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-21
- Publication Date
- 2024-12-13
AI Technical Summary
The existing all-inorganic perovskite solar cells are incompatible with the heat resistance of the flexible substrate when prepared at high temperatures, resulting in poor film quality and easy conversion to yellow phase without photovoltaic characteristics, affecting device efficiency.
The sulfonic acid-based ionic liquid additive is used in an inorganic perovskite film, and the solution spin coating is used to prepare at low temperature. The annealing temperature is reduced to below 100 °C to form a high-quality black phase film, using sulfonic acid groups and Cs ions to each other. The effect is to uniformize the distribution of Cs elements and reduce the energy barrier of the yellow phase transformation.
It realizes the preparation of high-quality all-inorganic perovskite black phase thin film stable at room temperature, improves device performance and bending stability, and solves the problem of incompatible flexible substrates and high-temperature preparation.
Smart Images

Figure CN119136565A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of low-temperature preparation of flexible all-inorganic perovskite solar cells, and in particular to a flexible all-inorganic perovskite solar cell prepared based on a sulfonic acid ionic liquid additive for reducing the phase transition temperature of the inorganic perovskite. Background Art
[0002] All-inorganic perovskite solar cells do not contain volatile organic cations, and their components are not easily degraded under high temperature and light, which has great commercial application value. However, due to the small ionic radius of Cs ions and the strong Cs-I interaction, the black phase transition temperature is relatively high (>340 ℃). At present, the strategy of using dimethylamine hydroiodide (DMAI) as an additive to form an intermediate phase to regulate the crystallization temperature has been widely used, and the device performance has been achieved by more than 22%. However, the inorganic perovskite film prepared under this strategy still requires high temperature conditions above 180 ℃, and it is impossible to prepare high-quality all-inorganic perovskite films with photovoltaic properties on PEN / PET flexible substrates (heat resistance temperature: 130~150℃). In addition, the film is more likely to transform into a yellow phase without photovoltaic properties at room temperature, which seriously affects the device efficiency. At present, the development of flexible all-inorganic perovskites is restricted by high-temperature preparation processes and is developing slowly. Therefore, it is very important to prepare inorganic perovskites with excellent device performance at low temperatures and more stability at room temperature, which is also a major challenge in the development of flexible all-inorganic perovskite devices. Summary of the invention
[0003] Based on this, the purpose of the present invention is to address the problem that the high preparation temperature of inorganic perovskite cells is incompatible with the heat resistance of flexible substrates, and to provide an inorganic perovskite solar cell prepared based on sulfonic acid ionic liquid additives. The additive can effectively reduce the phase formation temperature of the inorganic perovskite film to below 100°C, and the film quality is excellent with fewer defects. Finally, a flexible device of all-inorganic perovskite is successfully prepared, the device performance is good, and it has excellent bending stability.
[0004] The specific technical solution of the present invention is:
[0005] A flexible inorganic perovskite solar cell based on a sulfonic acid ionic liquid additive, the perovskite solar cell comprising: a flexible substrate, a hole transport layer, an inorganic perovskite film layer, an electron transport layer and an electrode layer stacked in sequence, the perovskite film layer is an inorganic perovskite material ABX3, wherein A is an inorganic ion cesium ion, B is Pb 2+ Sn 2+ and Ge 2+ Any one of, X is a halogen anion and SCN -One or more of the above, wherein a sulfonic acid ionic liquid-based additive is introduced into the film for preparation;
[0006] The flexible substrate is any one of a conductive polymer, a flexible glass, and a thin metal substrate;
[0007] The sulfonic acid ionic liquid additive is one or more of 1-propyl-3-methylimidazolium methanesulfonate, 1-propylsulfonic acid-3-methylimidazolium chloride, and 1-propylsulfonic acid-3-methylimidazolium hydrogen sulfate sulfonic acid ionic liquids;
[0008] The inorganic perovskite film is prepared in a glove box and deposited by solution spin coating, with an annealing temperature of up to 100° C. and a film thickness of 400-500 nm.
[0009] A method for preparing the above-mentioned perovskite solar cell comprises the following steps:
[0010] providing a flexible substrate;
[0011] forming a hole transport layer on the flexible substrate; and
[0012] forming the inorganic perovskite thin film layer on the hole transport layer; and
[0013] forming an electron transport layer on the inorganic perovskite thin film; and
[0014] A metal electrode layer is formed on the electron transport layer; wherein,
[0015] The formation of the perovskite thin film layer specifically includes:
[0016] AX and BX are dissolved in a solvent at a molar ratio of 1:1, and 10-20 mg / mL of a sulfonic acid ionic liquid additive is added to obtain a perovskite precursor solution, which is heated and stirred at 50-60 °C overnight; wherein A is an inorganic ion cesium ion, B is Pb 2+ Sn 2+ and Ge 2+ Any one of, X is a halogen anion and SCN - One or more of the following, the solvent is one or a mixture of N,N-dimethylformamide and dimethyl sulfoxide;
[0017] In a glove box, the perovskite precursor solution is spin-coated on an ITO flexible substrate using a coater at a speed of 3000-5000 rpm for 30-50 seconds, then annealed on a 60-70 °C heating table for 3-5 minutes, and then treated on a 90-100 °C heating table for 15-20 minutes to form a perovskite thin film layer.
[0018] Beneficial effects of the present invention: The sulfonic acid ionic liquid-based additive contains sulfonic acid groups, which have a strong interaction with Cs ions, can homogenize the distribution of Cs elements in perovskite, reduce the aggregation of Cs-rich films, and promote the combination of X ions in CsX with two-dimensional BX2 in the solution to form more [BX6] 4- , effectively reducing the energy barrier for the transformation of the yellow phase to the black phase of the all-inorganic perovskite, and forming a high-quality all-inorganic perovskite black phase film that is more stable at room temperature under conditions below 100 °C, thereby solving the temperature incompatibility problem between flexible substrates and inorganic perovskites prepared at high temperatures, and ultimately applied to all-inorganic perovskite flexible devices, achieving better device performance and excellent bending stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 It is a schematic diagram of the structure of the flexible perovskite solar cell of the present invention;
[0020] Figure 2 The figure is a schematic diagram of the interaction between the additive 1-propylsulfonic acid-3-methylimidazolium chloride and cesium iodide, and a graph showing the effect of the additive on the colloidal particle size of the precursor solution;
[0021] Figure 3 X-ray diffraction patterns of inorganic perovskite films with and without additives under unannealed conditions;
[0022] Figure 4 The two-dimensional distribution diagram of Raman spectrum and fluorescence spectrum of unannealed inorganic perovskite film with and without additives;
[0023] Figure 5 The surface morphology pictures of the films under different additives and the optical property curves of the films;
[0024] Figure 6 Performance curve and stability curve of flexible all-inorganic perovskite device. DETAILED DESCRIPTION
[0025] The flexible inorganic perovskite solar cell and its preparation process provided by the present invention will be further described below in conjunction with the accompanying drawings and embodiments.
[0026] See also Figure 1 The inorganic perovskite battery provided by the present invention includes: a flexible substrate 1, a hole transport layer 2, a perovskite film layer 3, an electron transport layer 4 and an electrode layer 5 which are stacked in sequence; the perovskite layer is prepared into a high-quality inorganic perovskite film at low temperature by adding a sulfonic acid ionic liquid as an additive in a precursor solution.
[0027] The concentration of the sulfonic acid ionic liquid additive in the perovskite precursor solution is 5-30 mg / mL. When used in perovskite solar cells, if the concentration of the additive is too low, the black phase transformation is incomplete, and if the concentration is too high, the series resistance of the perovskite film increases, affecting the device performance. Preferably, the concentration of the additive is 10-20 mg / mL.
[0028] In the perovskite-type ABX3 inorganic material, A is an inorganic Cs ion, and B is a Pb 2+ Sn 2+ ,Ge 2+ Any one of the following, X is a halogen anion or SCN - Preferably, B is Pb 2+ , X is Cl - Br - ,I - Since the lead-based inorganic perovskite of the pure iodine system does not have the problem of photoinduced halogen phase segregation, and its bandgap is 1.68-1.75 eV, it has the highest theoretical efficiency of all-inorganic perovskite cells, therefore, the inorganic perovskite material is further preferably CsPbI3.
[0029] The additive is one or more of sulfonic acid ionic liquids such as 1-propyl-3-methylimidazolium methanesulfonate, 1-propylsulfonic acid-3-methylimidazolium chloride, and 1-propylsulfonic acid-3-methylimidazolium hydrogen sulfate. Since the anion of 1-propylsulfonic acid-3-methylimidazolium hydrogen sulfate can further ionize H + , which has strong acidity and has an adverse effect on device performance, while the Cl - The perovskite lattice can be doped in trace amounts, which is beneficial to stabilize the all-inorganic perovskite lattice and improve the stability and efficiency of the device. Therefore, the additive is preferably 1-propylsulfonic acid-3-methylimidazolium chloride.
[0030] See also Figure 1 The present invention provides an inorganic perovskite solar cell, comprising a flexible substrate 1, a hole transport layer 2, an inorganic perovskite film 3, an electron transport layer 4 and a metal electrode 5 which are stacked.
[0031] The material of the substrate 1 is not limited, and can be any one of a conductive polymer, a flexible glass, and a thin metal substrate. ITO is a metal compound with excellent conductivity and high light transmittance, and is a commonly used transparent electrode material. Among these flexible substrate materials, polyethylene terephthalate (PET) and polyethylene naphthalate (PEN) are widely used as substrate materials for flexible devices due to their low cost, good bending performance, good optical transparency, and good chemical stability. Considering that PEN has higher heat resistance, the substrate 1 is preferably an ITO-PEN flexible substrate.
[0032] The hole transport layer 2 is poly[3-(methylamine butyrate)thiophene] (P3CT-N) with a thickness of 5-30 nm. Considering that the hole transport layer has a certain light absorption ability, the preferred thickness is 10 nm.
[0033] The inorganic perovskite film 3 has a thickness of 400-600 nm. Considering that a higher thickness of the perovskite layer causes greater carrier phase recombination, and a lower thickness results in less light absorption by the perovskite layer, the preferred thickness is 450 nm.
[0034] The additive is one or more of sulfonic acid ionic liquids such as 1-propyl-3-methylimidazolium methanesulfonate, 1-propylsulfonic acid-3-methylimidazolium chloride, and 1-propylsulfonic acid-3-methylimidazolium hydrogen sulfate. Considering the strong interaction between 1-propylsulfonic acid-3-methylimidazolium chloride and Cs ions, it can promote the detachment of I ions in the strongly bound CsI, thereby promoting the [PbI6] 4- The formation of CsPbI3 black phase transition energy barrier is reduced to achieve low-temperature preparation. 1-propylsulfonic acid-3-methylimidazolium chloride is added to the perovskite precursor solution, and the solution is spin-coated in a glove box, and a two-step gradient annealing process is performed to form a black phase inorganic perovskite film.
[0035] The electron transport layer 4 includes a PCBM layer, a C60 layer and a TPBi layer stacked in sequence. Considering the large energy level loss of perovskite and C60, a double electron transport layer of PCBM and C60 is used, and TPBi is a hole blocking layer. The thickness of the PCBM layer is 20-40 nm, the thickness of the C60 layer is 30-45 nm, the thickness of the TPBi layer is 6-10 nm, and the total thickness of the electron transport layer 4 is 50-100 nm. Because PCBM is easily soluble in chlorobenzene, and chlorobenzene has no destructive effect on perovskite, chlorobenzene is selected as a solvent and prepared by solution spin coating, which can effectively cover the holes that may exist on the surface of perovskite, and the preferred thickness is 20 nm. Both the C60 and TPBi layers are prepared by thermal evaporation vacuum coating, which can ensure that the film is more dense and uniform, and the preferred thicknesses are 30 nm and 6 nm, respectively.
[0036] The thickness of the electrode 5 is 80-200 nm, and the material is not limited. However, considering the conductivity and work function of the metal, the electrode is preferably an Ag electrode, and the preferred thickness is 100 nm.
[0037] Hereinafter, the perovskite film and the method for preparing the flexible perovskite solar cell will be further described through specific examples.
[0038] Example
[0039] like Figure 1 As shown, the inorganic perovskite solar cell includes a flexible substrate 1, a hole transport layer 2, an inorganic perovskite film 3, an electron transport layer 4 and a metal electrode 5 which are stacked in sequence, and the preparation method is as follows:
[0040] A 2cm×2cm ITO-PEN substrate was used as the flexible substrate 1. The flexible substrate was first adhered to a 2cm×2cm hard glass substrate with double-sided tape. The surface protective film of the flexible substrate was torn off with tweezers, and then a high-temperature conductive adhesive was used to cover the width of about 2mm at both ends of the ITO. Subsequently, the surface was wiped and rinsed with alcohol, and the substrate was blown dry with a nitrogen gun. It was used after being treated with UV ozone for 10 minutes.
[0041] On the treated ITO-PEN substrate, a hole transport layer 2 is deposited by solution spin coating. The transport layer 2 is a P3CT-N material layer, which is formed by spin coating of a methanol solution of P3CT-N, with a solution concentration of 1 mg / mL, a spin coating machine speed of 4000 rpm, a spin coating time of 30 seconds, and a thickness of 10 nm.
[0042] The inorganic perovskite film 3 is prepared on the hole transport layer 2 at low temperature, and the specific method is as follows:
[0043] Inorganic perovskite solution: 260 mg CsI, 461 mg PbI2 and 15 mg 1-propylsulfonic acid-3-methylimidazolium chloride were dissolved in 1 mL of a mixed solvent of dimethyl sulfoxide and N,N-dimethylimidamide, with a volume ratio of 7:3, and then stirred overnight at 60 °C and filtered with a 0.45 μm filter membrane before use. The inorganic perovskite film was prepared in a glove box by solution spin coating. The speed of the spin coater during spin coating was 4000 rpm and the spin coating time was 40 seconds. After the spin coating, the film was immediately placed on a 60 °C heating table for annealing for 4 minutes, and then further annealed at 90 °C for 20 minutes to form an inorganic perovskite film with a thickness of 450 nm.
[0044] The perovskite film was then passivated and post-treated by depositing an 8 mg / ml isopropanol solution of butanediamine on the perovskite film at a spin coating speed of 3000 rpm for 30 seconds, followed by annealing at 100°C for 5 minutes.
[0045] The electron transport layer 4 is fabricated on the perovskite film 3 by:
[0046] First, a 10 mg / mL PCBM chlorobenzene solution was spin-coated on the surface of the perovskite film by solution spin coating at a speed of 2000 rpm, a spin coating time of 45 seconds, and a thickness of 20 nm. Then, a 30 nm thick C60 layer and a 6 nm TPBi layer were sequentially deposited on the PCBM by vacuum thermal evaporation.
[0047] A layer of silver is deposited on the electron transport layer 4 by vacuum evaporation as an electrode 5 with a thickness of 100 nm.
[0048] See also Figure 2 , which is a schematic diagram of the interaction between the additive 1-propylsulfonic acid-3-methylimidazolium chloride of the present invention and cesium iodide, and a graph showing the effect of the additive on the colloidal particle size of the precursor solution. Figure 2 (a), (b) and (c) are the infrared spectra of the interaction between 1-propylsulfonic acid-3-methylimidazolium chloride and cesium iodide, and the X-ray photoelectron spectra of Cs 3d and S2p orbitals, respectively; (d) is a graph showing the change in colloidal particle size before and after the additive is added to the perovskite precursor solution. Figure 2 The shift in the binding energy between the sulfonic acid group and Cs in (a) and (b) indicates that 1-propylsulfonic acid-3-methylimidazolium chloride has a strong interaction with CsI, and Figure 2 The presence of the sulfonic acid metal salt peak in the S2p orbital in (c) further indicates that the Cs in CsI binds to the sulfonic acid group, thereby releasing free I ions, which in turn promote the I ions to bind to the two-dimensional long chain PbI2 in the solution to form [PbI6] 4- ,thus Figure 2 (d) The colloidal particles in the precursor solution are significantly reduced.
[0049] See also Figure 3 , which are X-ray diffraction patterns of inorganic perovskite films with and without additives under unannealed conditions. (a) Comparison of X-ray diffraction patterns of CsPbI3 film and CsI film with and without additives; (b) X-ray diffraction patterns of unannealed perovskite films under different concentrations of additives. Figure 3 This indicates that after adding 1-propylsulfonic acid-3-methylimidazolium chloride, Cs no longer aggregates in the perovskite film and the distribution of CsPbI3 becomes more uniform.
[0050] See also Figure 4 , are two-dimensional distribution diagrams of Raman spectra and fluorescence spectra of unannealed inorganic perovskite films with and without additives. (a) and (b) are two-dimensional Raman spectra distribution diagrams of unannealed perovskite films with and without additives; (c) and (d) are two-dimensional fluorescence spectra distribution diagrams of unannealed perovskite films with and without additives. Figure 4This further shows that the inorganic perovskite film with additives is more evenly distributed. Figure 2 The results in correspondence.
[0051] Figure 5 The following are the surface morphology pictures of the films under different additives and the optical characteristic curves of the films. (a) shows the effect of different concentrations of additives on the surface morphology of perovskite films; (b) and (c) show the X-ray diffraction and UV-visible absorption spectra of inorganic perovskite films with different concentrations; (d) shows the time-resolved photoluminescence spectra of films with and without additives. (a), (b) and (c) show that the addition of 1-propylsulfonic acid-3-methylimidazolium chloride can promote the formation of inorganic perovskite black phase, reaching the optimal concentration at 15 mg / mL. And (d) shows that the carrier lifetime of CsPbI3 is extended to more than 100 ns, which is also conducive to obtaining better device performance.
[0052] See also Figure 6 , which are the performance curves and stability curves of flexible all-inorganic perovskite devices. (a) and (b) are the JV curves of flexible all-inorganic perovskite solar cells prepared at high temperature 180 ℃ and low temperature 90 ℃, respectively, and flexible devices under the action of different concentrations of additives; (c) and (d) are the bending stability curves of flexible all-inorganic perovskite cells at curvature radii R = 5 mm and R = 3 mm, respectively. Figure 6 (a) shows that compared with the inefficiency of high-temperature flexible devices, the low-temperature prepared flexible all-inorganic perovskite battery can obtain better device performance under the action of sulfonic acid ionic liquid additives. Figure (b) shows that the device performance is optimal when the additive concentration is 15 mg / mL. (c) and (d) show that the all-inorganic perovskite device prepared by this low-temperature process has good flexibility and can achieve good bending performance.
Claims
1. A flexible inorganic perovskite solar cell based on sulfonic acid ionic liquid additive, characterized in that: The perovskite solar cell comprises: a flexible substrate, a hole transport layer, an inorganic perovskite film layer, an electron transport layer and an electrode layer stacked in sequence, wherein the perovskite film layer is an inorganic perovskite material ABX3, wherein A is an inorganic ion cesium ion, and B is Pb 2+ Sn 2+ and Ge 2+ Any one of, X is a halogen anion and SCN - One or more of the above, wherein a sulfonic acid ionic liquid-based additive is introduced into the film for preparation; The flexible substrate is any one of a conductive polymer, a flexible glass and a thin metal substrate; The sulfonic acid ionic liquid additive is one or more of 1-propyl-3-methylimidazolium methanesulfonate, 1-propylsulfonic acid-3-methylimidazolium chloride and 1-propylsulfonic acid-3-methylimidazolium hydrogen sulfate sulfonic acid ionic liquids; The inorganic perovskite film is prepared in a glove box and deposited by solution spin coating, with an annealing temperature of up to 100°C and a film thickness of 400-500 nm.
2. The inorganic perovskite solar cell according to claim 1, characterized in that: Its preparation specifically comprises the following steps: providing a flexible substrate; forming a hole transport layer on the flexible substrate; and forming the inorganic perovskite thin film layer on the hole transport layer; and forming an electron transport layer on the inorganic perovskite thin film; and A metal electrode layer is formed on the electron transport layer; wherein, The formation of the perovskite thin film layer specifically includes: AX and BX are dissolved in a solvent at a molar ratio of 1:1, and 10-20 mg / mL of a sulfonic acid ionic liquid additive is added to obtain a perovskite precursor solution, which is heated and stirred at 50-60 °C overnight; wherein A is an inorganic ion cesium ion, B is Pb 2+ Sn 2+ and Ge 2+ Any one of, X is a halogen anion and SCN - One or more of the following, the solvent is one or a mixture of N,N-dimethylformamide and dimethyl sulfoxide; In a glove box, the perovskite precursor solution is spin-coated on an ITO flexible substrate using a coater at a speed of 3000-5000 rpm for 30-50 seconds, then annealed on a 60-70 °C heating table for 3-5 minutes, and then treated on a 90-100 °C heating table for 15-20 minutes to form a perovskite thin film layer.
